Etty Hillesum or When God Doesn't Work - Mora Calvo, Hernán (2025)
Etty Hillesum developed throughout her life the task of self-knowledge and from there she discovered that life consisted of achieving a better dimension, always vitalized, be it of one’s own life and of the life of others. However, life is dry, dark and contradictory and sometimes offers enmities with itself. The question is, then, what does God do about it?